A regression discontinuity assessment of the differential impacts of China’s natural forest protection program across forestland property right regimes - Liu, Qi; Liu, Shilei; Liu, Zhaoyang; Deng, Xiangzheng; Xu, Jintao; Kontoleon, Andreas (World development, 2025)
•The NFPP has a moderately positive effect on forest cover.•Positive effects are larger for village-managed forests than for state-owned forests.•Redirecting a larger share of funds and restoration efforts toward village forest managers could enhance program performance.•Findings inform China's State Forest Property Reform, debating whether to strengthen SOFE worker rights or extend rights to village households. In 2000 China launched the Natural Forest Protection Program (NFPP) as its flagship initiative for forest conservation and restoration, targeting both state-owned forestland managed by state-owned forest enterprises (SOFEs) and large areas of forestland held by village households. This study evaluates the overall impact of the NFPP on forest cover and examines the program’s heterogeneous effects across property right regimes and provinces using a spatial regression discontinuity design. Our analysis reveals that forest cover within NFPP boundaries is, on average, about 6 % higher than in adjacent areas. Notably, collective forestland experiences an 82 % greater treatment effect compared to state-owned forests – even though collective areas receive less direct financial support – underscoring the role of institutional and local governance factors. Furthermore, our findings highlight significant regional variations in program outcomes. Overall, the NFPP exemplifies a proactive approach to reversing deforestation amidst rapid economic development, and our results offer valuable insights for refining policy measures and ensuring equitable funding strategies across diverse forest management regimes.